Effect of the DnaK chaperone on the conformational quality of JCV VP1 virus‐like particles produced in Escherichia coli. (3rd March 2014) - Saccardo, Paolo; Rodríguez‐Carmona, Escarlata; Villaverde, Antonio; Ferrer‐Miralles, Neus
<x xml:space="preserve">Abstract</x> Protein nanoparticles such as virus‐like particles (VLPs) can be obtained by recombinant protein production of viral capsid proteins and spontaneous self‐assembling in cell factories. Contrarily to infective viral particles, VLPs lack infective viral genome while retaining important viral properties like cellular tropism and intracellular delivery of internalized molecules. These properties make VLPs promising and fully biocompatible nanovehicles for drug delivery. VLPs of human JC virus (hJCV) VP1 capsid protein produced in Escherichia coli elicit variable hemagglutination properties when incubated at different NaCl concentrations and pH conditions, being optimal at 200 mM NaCl and at pH range between 5.8 and 7.5. In addition, the presence or absence of chaperone DnaK in E. coli cells influence the solubility of recombinant VP1 and the conformational quality of this protein in the VLPs. The hemagglutination ability of hJCV VP1 VLPs contained in E. coli cell extracts can be modulated by buffer composition in the hemagglutination assay. It has been also determined that the production of recombinant hJCV VP1 in E. coli is favored by the absence of chaperone DnaK as observed by Western Blot analysis in different E. coli genetic backgrounds, indicating a proteolysis targeting role for DnaK. However, solubility is highly compromised in a DnaK− E. coli strain suggesting an important role of this chaperone in reduction of protein aggregates. Finally, hemagglutination efficiency of recombinant VP1 is directly related to the presence of DnaK in the producing cells. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:744–748, 2014